Draft Annual Plan 1973-74 Volume II (Statements) Government of Bihar - Planning Commission (Planning Commission, 1972)
A Thermal power station consisting of three 15 MW units and two 50 units is under operation at Barauni, However, the Present generating capacity of this power station will not be able to meet the growing demands of North Bihar. A Committed was set up by the Govt, of India to examine the feasibility for installing further generating units in North Bihar to cope up with load demands by the end of Fourth Five Year Plan period The studied the problem and recommended for (a) augmentation of Barauni Thermal Power Station by x 2 z60 MW end (b) installation of a new Thermal power station e.t Muzaffarpur with a capacity of 4 x 6 CMW.
Planning Department Government of Bihar